2003
DOI: 10.1242/dev.00514
|View full text |Cite
|
Sign up to set email alerts
|

The glial sling is a migratory population of developing neurons

Abstract: For two decades the glial sling has been hypothesized to act as a guidance substratum for developing callosal axons. However, neither the cellular nature of the sling nor its guidance properties have ever been clearly identified. Although originally thought to be glioblasts, we show here that the subventricular zone cells forming the sling are in fact neurons. Sling cells label with a number of neuronal markers and display electrophysiological properties characteristic of neurons and not glia. Furthermore, sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 53 publications
3
73
0
Order By: Relevance
“…4F), and over time more cells within this population were observed closer to the midline ( Fig. 4L; labeled with calretinin), suggesting that the population of cells may be migrating toward the midline as they do in mouse (Shu et al, 2003c). At the same developmental stage, a second Nfia-positive population was evident more dorsally in the region of the indusium griseum (Fig.…”
Section: Key Midline Structures Are Present In Developing Human Brainmentioning
confidence: 88%
See 1 more Smart Citation
“…4F), and over time more cells within this population were observed closer to the midline ( Fig. 4L; labeled with calretinin), suggesting that the population of cells may be migrating toward the midline as they do in mouse (Shu et al, 2003c). At the same developmental stage, a second Nfia-positive population was evident more dorsally in the region of the indusium griseum (Fig.…”
Section: Key Midline Structures Are Present In Developing Human Brainmentioning
confidence: 88%
“…Several markers are known to be specific for the subcallosal sling in mouse, including NeuN, Nfia, and calretinin (CR) (Shu et al, 2003c), and all three were used to examine the presence of the subcallosal sling in coronal sections of human fetal brains aged 13, 15, and 17 weeks of gestation (Fig. 4).…”
Section: Key Midline Structures Are Present In Developing Human Brainmentioning
confidence: 99%
“…Cortical commissural axons rely on cues provided by a population of cells named the "glial sling" to successfully navigate the midline. Neurons that form the glial sling derive from the SVZ and migrate toward the midline around E17.5, just before the arrival of the first commissural axons (Shu et al 2003b). In mouse mutants for one of the Nuclear factor I genes, Nfia, sling cells fail to reach the midline and instead migrate toward the septum.…”
Section: Migration Of Guidepost Cells For Axon Guidancementioning
confidence: 99%
“…8). An additional mechanism of guidance at the cortical midline occurs via transient neuronal populations that form the subcallosal sling and a cellular corridor for callosal axons to cross the midline (Shu et al, 2003b;Niquille et al, 2009). We stained sections from both KOs and WT littermates with antibodies against the transcription factor Nfia, which labels the subcallosal sling (Shu et al, 2003a) and found it to be intact in both Slc12a6…”
Section: ⌬18/⌬18mentioning
confidence: 99%